Mechanistic study of co2 corrosion related to corrosion in oil and gas exploration and production - Mohd.Halimi, Azman (2013)
A mechanistic model of CO2 corrosion in the presence of H2S has been developed. A model has been developed for the computation of corrosion rates of carbon steels in presence of carbon dioxide and hydrogen sulfide. The model included an electrochemical model for partial cathodic and anodic process on the metal surface. The partial processes taken into account by the model include the oxidation of iron and reduction of hydrogen ions, water, carbonic acid and hydrogen sulfide. The model has been verified by comparing calculated corrosion rates with corrosion model prediction software. The corrosion model prediction software consists of Freecorp, Norsok, Cassandra and ECE. The effects of various conditions such as temperature and pH value on corrosion rates has been analyze. The trends shown in the predictions agreed well with the general understanding of the CO2 corrosion process in the presence of of H2S.